The Influence of Realistic Mathematical Approaches on The Ability to Understand Mathematical Concepts of Grade VII Students of SLB-B Negeri Mandiraja - Luthfi Nofiana Istiqumatunisa; Zakkiyatul Darojah Jemar (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
Based on the results of interviews with mathematics teachers at SLB Negeri Madiraja, it shows that students have not been able to understand the concept of mathematics properly. The purpose of this study is to analyze the influence of realistic mathematical approaches on the ability to understand mathematical concepts of SLB-B students in Mandiraja State. The type of research is in the form of quantitative research with a research design of one group pre-test post-test which uses a sampling technique in the form of saturated sampling. Based on a comparison of pre-test and post-test scores with a range of values of 0 to 27, the highest pre-test score is 10 and the lowest score is 7, resulting in an average score of 8.5, while the highest post-test score is 25 and the lowest score is 22, resulting in an average score of 21.5. The calculation of the N-Gain test yielding an average of 0.798 is included in the high criterion. This shows the influence of the realistic mathematical approach on the ability to understand mathematical concepts of grade VII students of SLB-B Negeri Mandiraja on multiplication material.